Melatonin alleviates liver steatosis induced by prenatal dexamethasone exposure and postnatal high-fat diet - Tsai, Ching-Chou (Exp Ther Med, 2018)
Prenatal exposure to glucocorticoids is associated with negative health consequences for the offspring that persist into adulthood, including liver steatosis. Melatonin has previously been demonstrated to suppress liver steatosis and oxidative stress in humans with non-alcoholic fatty liver disease and in animal models of obesity. The present study aimed to determine whether melatonin protects against liver steatosis induced by prenatal dexamethasone exposure followed by postnatal high-fat diet. Pregnant Sprague-Dawley rats at gestational days 14–21 were administered dexamethasone (0.1 mg/kg/day) or saline via intraperitoneal injection. The offspring were then divided into five groups, as follows: Vehicle, postnatal high-fat diet (VHF), prenatal dexamethasone exposure (DEX), prenatal dexamethasone exposure + postnatal high-fat diet (DHF), and prenatal dexamethasone exposure + postnatal high-fat diet + melatonin (DHFM) group. Following vehicle or dexamethasone exposure of the maternal rats, the offspring rats in the VHF, DHF and DHFM groups received a high-fat diet (58% fat) between weaning and 6 months of age. In the DHFM group, melatonin was administered to the mothers from gestational days 14–21 until weaning. The offspring continued to receive melatonin until they were sacrificed at 6 months old. Oil Red O staining demonstrated stronger intensity in the DHF group compared with that in the other four groups. Western blot analysis also revealed higher levels of cleaved caspase-3, tumor necrosis factor-α (TNF-α), suppressor of cytokine signaling 3 (SOCS3) and malondialdehyde (MDA), as well as reduced expression of manganese superoxide dismutase (MnSOD) and phosphoinositide 3-kinase (PI3K) in the DHF group compared with the vehicle and DHFM groups. In addition, melatonin reduced the Oil Red O staining intensity and the levels of cleaved caspase-3, TNF-α, SOCS3 and MDA, while it increased the MnSOD and PI3K levels, in the DHFM group compared with the DHF group. In conclusion, postnatal high-fat diet aggravated the prenatal dexamethasone-induced liver steatosis in adult rat offspring via inflammation, oxidative stress and cellular apoptosis, which may be ameliorated by prenatal melatonin therapy.